Quantitative strategy planning matrix in supporting sustainability of pearl millet (Pennisetum glaucum) farming - Ikawati Karim; Edy Fitriawan Syahadat; Rahman Basri (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2019)
Pearl millet is not only a potential source of income for farmers but can also support the availability of alternative local food in West Sulawesi. As a potential local food, pearl millet contains good nutrition such us anti-oxidant, bioactive compound and fiber. This research is aim to analyze the internal and external factors, IE matrix and then Quantitative Strategy Planning Matrix (QSPM) in order to figure out the priority strategies of pearl millet (Pennisetum glaucum) farming. This research was conducted in West Sulawesi by investigating pearl millet farmers in the production center. The strategy that could be applied is how to support an aggressive growth-oriented strategy. The priority strategies to be implemented are 1) procurement of farming equipment to increase production and productivity, 2) maximizing land potential through efficient farming input, 3) supporting farmers to keep trying to grow pearl millet in an effort to produce alternative food, 4) the use of environmentally friendly farming equipment and input technologies to support sustainability, 5) training to the pearl millet farmers on processing and diversification of pearl millet into industrial products, 6) building adequate infrastructure to facilitate distribution and marketing, 7) plotting pearl millet as a potential superior local food in West Sulawesi, 8) facilitating to access to capital by activating rural-based microfinance institutions, 9) increasing the capacity of farmers and village stakeholders through institutional strengthening, counseling and training and 10) introducing pearl millet to the market and consumers as a local food that is rich in fiber and high antioxidants.